Association of Transcranial Doppler Microembolic Signal With Short‐Term Mortality in Acute Ischemic Stroke and Active Cancer - Sono Toi; Eiko Higuchi; Megumi Hosoya; Satoko Arai; Kentaro Ishizuka; Takafumi Mizuno; Takao Hoshino; Yukiko Tsutsumi; Kazuo Kitagawa (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aimed to clarify the characteristics and survival prediction value of transcranial Doppler microembolic signals (MES) in patients with acute cerebral infarction and active cancer. Methods and Results Between 2017 and 2022, 1089 cases of acute cerebral infarction were recorded within 7 days of disease onset. Among them, transcranial Doppler was successful in 33 patients who had active cancer, and these data were analyzed in this study. The primary outcomes were stroke recurrence and mortality at 3 months. The study population had the following characteristics [median (interquartile range)]: age, 70 years (63–78); body mass index, 21.6 (20–24), National Institutes of Health Stroke Scale 3 (1–6), and modified Rankin Scale score at discharge 1 (1–4). The most common cancer types were lung (24%), pancreatic (24%), and intestinal (18%). MES was present in 16 of 33 patients (48.5%). The presence and number of MES were significantly associated with the levels of D‐dimer (P <0.001) and C‐reactive protein (P=0.012). Moreover, the presence of MES was associated with multiple ischemic lesions and the 3‐territory sign on magnetic resonance imaging. Of the 33 patients, 9 died at 3 months, and 1 had stroke recurrence. On Cox multivariate analysis, using the MES‐negative group as a reference, the presence of MES was significantly associated with all‐cause death (adjusted hazard ratio, 12.19 [95% CI, 1.45–216.85]; P=0.020). Conclusions In patients with acute ischemic stroke and active cancer, the presence of MES was associated with D‐dimer and C‐reactive protein levels and multiple and 3‐territory ischemic lesions, and was predictive of short‐term survival.